Non-Denominational Spiritual Care Givers and the Development of their Spirituality. (25th February 2021) - ten Napel-Roos, Nelleke; Mathijssen, Brenda; Smeets, Wim; Zock, Hetty
Abstract : In the Netherlands, a growing number of spiritual care givers are working without being endorsed by any church or worldview organization. Since 2015, these non-denominational spiritual care givers can undergo an assessment of their "spiritual competence" on top of their Master's degree in Spiritual Care, which leads to a mandate in this area. This enables them to obtain full membership of the professional Association of Spiritual Caregivers in the Netherlands (Vereniging van Geestelijk VerZorgers, VGVZ), from which they previously were excluded. The VGVZ seeks to secure the quality and professionalism of spiritual care, and full membership is a condition typically required by clients or employers. The VGVZ's Professional Standard outlines the membership criteria and states that a spiritual care giver needs to have both a certain expertise, derived from a Master's degree, and authorization, derived from an endorsement or mandate that ought to safeguard their spiritual competence and authentic, lived spirituality. However, as this study illustrates, the terminology used in the Professional Standard is rather unclear. Reference is made to "spiritual", "worldview" and "hermeneutic" competencies, which are all situated in the domain of substantive, process-orientated and personal capabilities. This article critically examines the notion of spiritual competence as a leading concept in the acceptance and assessment of non-denominational spiritual care givers. By doing so, it offers a novel systematic analysis of the field and sets the agenda for future research.